Effect of bed materials on slagging and fouling during Zhundong coal gasification. Issue 5 (September 2017) - Qi, Xiaobin; Song, Guoliang; Song, Weijian; Yang, Shaobo
The suitable bed material is important to inhibit ash-related problems including agglomeration and slagging in furnace and fouling on tail heated surfaces during coal gasification in fluidized bed. For newfound high-alkali vast-reserve Zhundong coal in China, the selection of bed material in fluidized bed should be paid more attention because of its more serious ash-related issues. Five bed materials including quartz, kaolin, corundum, sludge ash, and phosphate rock were used to investigate their feasibility to solve the ash-related issues of two typical types of Zhundong coal including Tianchimulei coal and Shaerhu coal. All of five bed materials could effectively impact the release and transformation of alkali and alkaline earth metal species, especially Na species. The capture order of Na by five bed materials from high to low was sludge ash, quartz, kaolin, corundum, and phosphate rock for the two types of coal, and ash fusion temperatures of residual ash added different bed materials were in orders of phosphate rock > corundum > sludge ash >kaolin > quartz for Tianchimulei coal and corundum > phosphate rock > sludge ash > kaolin >quartz for Shaerhu coal. This influence of bed materials was mainly related to their chemical compositions, especially Al-, Si-, and P-based compounds. Due to the strong capture of alkali and alkaline earth metal-based compounds and high ash fusibility temperature, sludge ash was suggested as the appropriate selection of the bed material during Zhundong coal gasification in fluidized bed. Moreover, this suggestion would contribute to the sewage sludge treatment.